Optimization of Calcium- Enriched Cookies Incorporating Eggshell and Shiitake Powder - Roshan Kunwar; Bishal Thagunna; Smriti Paudel; Anjana Lamichhane; Apekshya Bhattarai; Sandhya Subedi (Biology, Medicine, & Natural Product Chemistry, 2026)
Eggshells from chickens can serve as a source of dietary calcium. This research examined the impact of incorporating eggshell powder on the proximate, mineral, and sensory characteristics of cookies. The cookies were made using wheat flour, enhanced with eggshell powder in proportions of 3, 5, 7, and 9%, along with shitake mushroom powder in amounts of 3, 4, 5, and 6%. The samples were labeled as A, B, C, D and E. The dough was prepared using a multi-stage mixing technique, like the creaming method. After that, it was shaped into round cookies, which were baked in a preheated oven at 180 oC for 25 minutes. The results obtained showed that incorporating eggshell powder significantly raised the calcium levels in the cookies, measuring 1085.05, 1505.20, 1975.22, and 2450.11 mg/100g at concentrations of 3%, 5%, 7%, and 9%, respectively. Additionally, there is a slight alteration in the texture and sensory characteristics of the cookies. The iron content of cookies containing shitake mushroom powder at 3, 4, 5, and 6 % were 3.50, 3.41, 3.36, and 2.28 mg/100g respectively. The proximate analysis revealed that adding eggshell and shiitake mushroom powder increased the protein content from 8.83% to 14.67%, the ash content from 1.56% to 4.59%, and the fiber content from 0.92% to 2.88%. Simultaneously, it reduced the moisture content from 5.78% to 4.69% and the fat content from 19.03% to 15.93%. To summarize, adding eggshell powder and shiitake mushroom could improve the nutritional profile of traditional cookies, particularly in terms of calcium, ash, fiber, and protein levels.